Incidental Finding of Goblet Cell Adenocarcinoma Post Appendectomy: A Rare Case Report - Naushad, Fathima Hana Mohamed; Alam, Shameema; Ishaq, Aliya (Dubai Medical Journal, 2025)
Introduction: One of the most frequent etiologies of an acute abdomen is appendicitis, which ranks as one of the primary reasons for surgical emergencies globally. Goblet cell adenocarcinoma (GCA) of the appendix, is hallmarked for displaying both endocrine and exocrine traits, presenting with symptoms similar to acute appendicitis, complicating its diagnosis before surgery. Case Report: We present a case report of a 61-year-old male with a medical history of benign prostatic hyperplasia and depression who presented lower abdominal pain, fever, and diagnosed with acute appendicitis. A laparoscopic appendectomy was performed. Histopathology revealed GCA of the appendix with Ki-67 proliferative index of 10%. After multidisciplinary team (MDT) discussion and further evaluation, he underwent a right colectomy and hyperthermia intraperitoneal chemotherapy (HIPEC). Conclusion: Goblet cell tumors are rare and often not readily recognized. A multidisciplinary approach including a team of oncologists, pathologists, radiologists, and general surgeons is essential for the intricacy of diagnosis and therapy. Patients undergoing appendectomy due to appendicitis need a thorough evaluation of biopsy specimen to exclude malignancy.